2019
DOI: 10.3390/f10111043
|View full text |Cite
|
Sign up to set email alerts
|

PacBio Long-Read Sequencing Reveals the Transcriptomic Complexity and Aux/IAA Gene Evolution in Gnetum (Gnetales)

Abstract: The genus Gnetum includes pantropical trees, shrubs and lianas, with unresolved phylogenetic relationships with other seed plant groups. Despite the reference genome for this genus being recently published, the molecular mechanisms that regulate the reproductive organ development of Gnetum remain unclear. A previous study showed that indole-3-acetic acid is involved in the regulation of female strobili of Gnetum, while the diversity and evolution of indole-3-acetic acid-related genes—the Aux/IAA genes—have nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(44 citation statements)
references
References 111 publications
5
39
0
Order By: Relevance
“…Structural analysis of the full-length transcriptome AS and APA analysis A total of 8,512 genes were identi ed as having at least one poly(A) site, suggesting that alternative polyadenylation may enrich the proteomic complexity and affect the seed ripening process of G. luofuense. Previous studies have suggested that alternative polyadenylation affects the development of G. luofuense leaves and female strobili [29,41]. In addition, we found considerable differences in the number of AS events among different gymnosperm species and among different organs in the same species by comparing AS events in the leaves of G. biloba (12,209) [42] and the leaves (12,998) [41], female strobili (10,454) [29], and seeds of G. luofuense (9,061, the present study).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Structural analysis of the full-length transcriptome AS and APA analysis A total of 8,512 genes were identi ed as having at least one poly(A) site, suggesting that alternative polyadenylation may enrich the proteomic complexity and affect the seed ripening process of G. luofuense. Previous studies have suggested that alternative polyadenylation affects the development of G. luofuense leaves and female strobili [29,41]. In addition, we found considerable differences in the number of AS events among different gymnosperm species and among different organs in the same species by comparing AS events in the leaves of G. biloba (12,209) [42] and the leaves (12,998) [41], female strobili (10,454) [29], and seeds of G. luofuense (9,061, the present study).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that alternative polyadenylation affects the development of G. luofuense leaves and female strobili [29,41]. In addition, we found considerable differences in the number of AS events among different gymnosperm species and among different organs in the same species by comparing AS events in the leaves of G. biloba (12,209) [42] and the leaves (12,998) [41], female strobili (10,454) [29], and seeds of G. luofuense (9,061, the present study). It is noteworthy that intron retention constituted the largest proportion of identi ed AS events in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations